Water filter system for car wash / Amirul Hakim Ramli ... [et al.] - Ramli, Amirul Hakim; Anak Sendol, Olivera Winsky; Mohammad Halim, Muhammad Ameer Izzat; Mat Jusoh, Ahmad Ammar; Mohd Ezan, Danish Ashman; Ibrahim, Muhammad Haikal; Thominathan, Santhanamery (2022)
World Water Day is held on 22 March every year and 2017's theme was ‘Wastewater, Why waste water?’. The campaign raises awareness about the importance of protecting this scarce but essential resource for economic, social, and environmental development. Water is the most essential element next to air for our survival. Water provides goods (drinking water, irrigation water) and services (hydroelectricity generation, recreation, and amenity) that are utilized by agriculture, industry and households. The provision of many of these goods and services is interrelated, determined by the quantity and quality of available water. Management and allocation of water entails consideration of its unique characteristics as a resource. There is a tremendous increase in water demand due to many factors such as growing population, increased agricultural needs, industrial use of water, water needed for electricity production, etc. This increased demand for water combined with the pollution of water will have many adverse effects on the environment, growth, and economy of the nation. The challenge of today is to learn how to use our water wisely. This challenge is greater now than ever before as industry and population continue to grow. Conservation will not only save our water supply but will also save us money. In this contest recycling of water may be considered as one of the most effective ways of water conservation. As such this project will introduce a system that can recycle car wash water to be reused for a new car wash. With a recycled water system, wastewater from car wash centers can be restored clean enough to be used again for future washes. This reduces the usage of freshwater and reduces the amount of waste you are releasing into the environment. The benefits are to reduce the business costs and increase profits.